Efektivitas Pembelajaran Etika Profesi dengan Menggunakan Metode Diskusi Melalui Aplikasi Whatsapp - Triwahyuni, Suri (Ridwan Institute, 2021)
This research aims to improve the effectiveness of students in receiving Professional Ethics lessons by applying discussion methods through whatsapp application assisted with powerpoint media, so that students' learning outcomes achieve the expected goals. This research was conducted at SMK Negeri 1 Singkep. The research used is class action research, which consists of pretest and postest. Success indicators can be seen from the evaluation of assessments on the I and test II tests. The results of the study using the discussion method through whatsapp application assisted with powerpoint media showed that students who achieved the Minimum Completion Criteria (KKM) were 91% and that were not complete 9%. While the response of learners to the effectiveness of professional ethics learning professional ethics learning using the method of discussion through the WhatsApp application assisted by powerpoint media 97% and the implementation of discussions by 91% with the ratio of interaction between groups to comment on each other by 5. Based on this research, it can be concluded that the learning of Professional Ethics by using discussion method through WhatsApp application assisted by powerpoint media in grade X students of SMK Negeri 1 Singkep banking year 2020/2021 has been very effective based on the learning outcomes of learners, and student responses.